PENGARUH PELAKSANAAN RISK BASED INTERNAL AUDITING TERHADAP PENCEGAHAN FRAUD - Dewi Yuniarti Rozali, Rozmita; Mohammad, Jabbaar (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to determine the effect of implementation of risk based internal auditing on fraud prevention on internal audit Inspection Office Bank BRI Bandung Region. The sample used by 18 internal auditors in Inspection Office of Bank BRI Bandung Region saturated sampling method. Based on calculation of simple regression analysis obtained result that every increase of implementation of risk based internal auditing (X) will lead to increase fraud prevention (Y). It shows that there is a positive influence between the implementation of risk based internal auditing on fraud prevention on the internal audit of Inspection Office of Bank BRI Bandung Region.